Polymeric Nanomedicines Based on Poly(lactide) and Poly(lactide-co-glycolide) - Tong, Rong (2013)
Small molecule chemotherapeutics often have undesired physiochemical and pharmacological properties, such as low solubility, severe side effect and narrow therapeutic index. To address these challenges, polymeric nanomedicine drug delivery technology has been routinely employed, in particular with the use of biodegradable and biocompatible polyesters, such as poly(lactide) (PLA) and poly(lactide-co-glycolide) (PLGA). Here we review the development and use of PLA and PLGA for the delivery of chemotherapeutic agents in the forms of polymer-drug conjugates and nanoconjugates.